1991
DOI: 10.1080/00224545.1991.9924646
|View full text |Cite
|
Sign up to set email alerts
|

Bullying among Australian School Children: Reported Behavior and Attitudes toward Victims

Abstract: The extent of bullying among Australian school children and attitudes toward victims of bullying were investigated in a survey of Australian school children between the ages of 6 and 16 years (n = 685) and their teachers (n = 32). Approximately 1 child in 10 was subjected to peer group bullying. Boys reported being bullied more often than girls, who tended to be more supportive of victims. With increasing age, there was a slight but significant decline in reported bullying; notably, however, attitudes toward v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
362
7
23

Year Published

1997
1997
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 493 publications
(430 citation statements)
references
References 4 publications
38
362
7
23
Order By: Relevance
“…These data are seen as positive, because t, in general, the bystander deals with the violence daily and remains silent due to the fear of becoming the next victim of the aggressor 27 . In addition, the data of this study also indicated that the number of boys and girls who helped peers was quite similar, going against the literature that points to girls as being the ones to mainly assume this role 4,28,29 . The data from this study also showed a strong association between being a spectator and other roles in bullying at school, especially with also being the aggressor.…”
supporting
confidence: 48%
“…These data are seen as positive, because t, in general, the bystander deals with the violence daily and remains silent due to the fear of becoming the next victim of the aggressor 27 . In addition, the data of this study also indicated that the number of boys and girls who helped peers was quite similar, going against the literature that points to girls as being the ones to mainly assume this role 4,28,29 . The data from this study also showed a strong association between being a spectator and other roles in bullying at school, especially with also being the aggressor.…”
supporting
confidence: 48%
“…Another possible explanation may be that the negative stigma perceived by their peers could hinder the bystanders' willingness to help the victim. Rigby and Slee (1991) found that many children and young people look down on children who are bullied because they are perceived as too "needy" and "demanding." This potential stigma may greatly increase their chance of being rejected by their peers.…”
Section: Discussionmentioning
confidence: 99%
“…Women are reported to have a greater capacity for empathy than men, both in recognizing the emotion of others and experiencing the emotion themselves [Grover and Brockner, 1989;Hoffman, 1977]. Empathy is reported to be a component in the moderation of attitudes, particularly those that relate to the victims of aggression [Rigby and Slee, 1991], with women reporting more positive attitudes towards victims than men [Ireland, 1999]. Although research has not focused on attitudes of forensic staff towards the victims of self-harm, it could be argued that sex differences should be expected with women, as a consequence of their increased capacity for empathy, more likely to demonstrate understanding attitudes towards those who self-harm.…”
Section: Introductionmentioning
confidence: 99%